2013
DOI: 10.1159/000347066
|View full text |Cite
|
Sign up to set email alerts
|

Public Awareness of Early Symptoms of Stroke and Information Sources about Stroke among the General Japanese Population: The Acquisition of Stroke Knowledge Study

Abstract: Background: It is important that the general population be aware of the early symptoms, since it has been shown that early arrival to hospitals leads better prognosis of stroke patients. However, the general population is not well informed about the early symptoms of stroke. This study was conducted to clarify which stroke symptoms are less well known and which information sources are related to awareness of stroke symptoms. Methods: A multiple-choice, mail-in survey involving 5,540 randomly selected residents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 20 publications
3
33
0
2
Order By: Relevance
“…The symptom that was least recognized was amaurosis fugax, which was present only in 15%; this is similar to what other studies have found [26]. Extrapolating these data to patients insured by INSSJP from Buenos Aires would suggest that 270,000 people might not be able to identify early symptoms of stroke.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The symptom that was least recognized was amaurosis fugax, which was present only in 15%; this is similar to what other studies have found [26]. Extrapolating these data to patients insured by INSSJP from Buenos Aires would suggest that 270,000 people might not be able to identify early symptoms of stroke.…”
Section: Discussionsupporting
confidence: 83%
“…30% of patients could not identify a single symptom suggestive of stroke. We found no association between knowing the risk factors or warning signs and appropriately endorsing calling 911 [18,26]. …”
Section: Discussionmentioning
confidence: 99%
“…In a population-based structured telephone survey of Japanese adults, 23% were able to correctly identify 5 early signs of stroke from among 10 listed symptoms with decoy choices [53]. A survey of high school students from Sargodha, Pakistan revealed a greater understanding of stroke symptoms among female students (61 vs. 30%).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that intermittent long-term intervention was effective in increasing the knowledge about early symptoms of stroke, but short-term intervention was less effective. 16 Multimedia campaigns are powerful for improving the knowledge about stroke, [9][10][11][12][13] and nowadays there are many healthcare programs and news bulletins of recent medical breakthroughs on television. It can be possible to negotiate with the producers of these programs, but many television campaigns usually require content to be produced on a commercial basis, and are bound by audience ratings.…”
Section: Discussionmentioning
confidence: 99%
“…13 Of 5509 individuals who agreed to participate in the postintervention survey, 3926 individuals responded to the postintervention mailed survey. In consequence, a response rate was 71.3% in total, 73.8% (1719/2329) in the intensive intervention area, 71.4% (1116/1562) in the moderate intervention area, and 67.4% (1091/1618) in the control area (P<0.001 for χ 2 test).…”
Section: Participantsmentioning
confidence: 99%